2020 Neonatal Nurse Practitioner Workforce Survey: An Executive Summary. (June 2021) - Snapp, Barbara; Moore, Tiffany A.; Wallman, Carol; Staebler, Suzanne
Abstract : Background: The National Association of Neonatal Nurse Practitioners (NANNP) partnered with the National Certification Corporation (NCC) to invite all NCC-certified neonatal nurse practitioners (NNPs) to participate in a national survey on NNP compensation, workforce environment, and satisfaction measures. Purpose: To understand the current NNP compensation, benefits, and workforce environment. Methods: An anonymous survey was sent to 6558 board-certified NNPs with 845 respondents. Results: Most of the survey respondents (92%) are in direct patient care (n = 804) with 83% (n=703) working full time (35 hours or more). Those NNPs with less than 5 years' experience had a mean salary of 119, 000 per year while more experienced NNPs (30-plus years) earned a mean salary of 134, 000 per year. Half of the NNPs (51%) report high satisfaction with their scope of practice and role in their organization. Distribution of NNPs throughout the workforce is suboptimal, with 67% of the administrators indicating they do not have enough NNPs. Implications for Practice and Research: The 2020 NANNP workforce survey collected information on NNP compensation, benefits, work environment, and experiences. It identified areas of satisfaction, such as compensation with bonuses and pay increases, and acknowledged areas needing improvement such as the lack of diversity within the profession. Utilizing the results of the survey will help create a more diverse, well-educated, and informed workforce to ensure culturally competent NNPs remain relevant within the healthcare system.